Association of COVID-19 Lockdown With Increased Rate of Cyclops Syndrome in Patients With Unexpected Home-Based Self-Guided Rehabilitation After ACL Reconstruction. Issue 2 (24th February 2023) - Bouguennec, Nicolas; Orce, Aida; Laboudie, Pierre; Pelletier, Simon; Dexhelet, Jeremy; Graveleau, Nicolas
Background: The risk of cyclops syndrome increases significantly after anterior cruciate ligament (ACL) reconstruction (ACLR) if complete extension is not recovered before the sixth postoperative week. The lockdown in France due to the COVID-19 pandemic led to an absence of supervised rehabilitation, requiring unexpected self-rehabilitation in patients who underwent ACLR just before lockdown. Purpose: To determine the rate of cyclops syndrome after ACLR in patients who underwent self-rehabilitation during lockdown. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 75 patients receiving a hamstring graft for ACLR during the COVID-19 pandemic between February 10, 2022, and March 16, 2020, carried out self-rehabilitation during part of their first 6 postoperative weeks using exercise videos on a dedicated website. Clinical examination was performed at a minimum 1-year follow-up with International Knee Documentation Committee (IKDC), Lysholm, Tegner, and ACL–Return to Sport after Injury (ACL-RSI) scores. This group was compared with a matched-pair control group of 72 patients who underwent surgery in 2019 and completed postoperative supervised rehabilitation with a physical therapist. Rates and reasons for second surgery (arthrolysis, meniscal procedure) were also recorded. Results: In the COVID group (n = 72; 3 patients were lost to follow-up), the mean follow-up was 14.5 ± 2.1 months (range, 13-21) and rate of reoperation for clinical cyclops syndrome was 11.1% (n = 8). The rate of cyclops syndrome was significantly lower (1.4%) in the control group ( P = .01). In the COVID group, 8 patients underwent anterior arthrolysis at a mean of 8.6 months after the primary surgery, and 4 patients underwent another surgical intervention (meniscal procedure [n = 3], device removal [n = 1]). In the COVID group, mean Lysholm was 86.6 ± 14.1 (range, 38-100), Tegner was 5.6 ± 2.3 (range, 1-10), subjective IKDC was 80.3 ± 14.7 (range, 32-100) and ACL-RSI score was 77.3 ± 19.7 (range, 33-100). Conclusion: The rate of cyclops syndrome after ACLR was significantly greater in the COVID group versus the matched controls. The dedicated website was not effective at supporting self-guided rehabilitation and could benefit from interactive improvements so it is at least as effective as supervised rehabilitation.